Perencanaan Strategis Sistem Dan Teknologi Informasi Pada Bank Sampah Kota: Studi Kasus Bank Sampah Kota Prabumulih - Eka Sri Wahyuni (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
Waste today is the most influential factor on the environment, it can not be denied that the waste will always exist as long as the activity of life is still running. Law no. 18 Year 2008 on trash management explains about the need to change the pattern of conventional trash management into trash management which is based on trash reduction and handling. The role of Bank Trash becomes important as one of the organizations that is expected to be able to carry out the task to be able to provide an active solution to the trash problem in Prabumulih City. This study aims to analyze the condition of information systems and information technology (IS / TI), in the Trash Bank environtment. Trash Bank Prabumulih City was chosen as the object of research because the existence of garbage bank becomes a very important requirement at this time. The literature review is used as a method in reviewing journals to determine the role of information systems and information technology (IS / IT) in optimizing interactions between organizations, customers and the wider community. This research produces information about the condition of information system and information technology (IS / IT) in Prabumulih Trash Bank so it can help give solution in an effort to increase the role of Information System and Information Technology in supporting the operational activity of Prabumulih Trash Bank.